2005
DOI: 10.1103/physrevb.72.214523
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity induced by spark erosion inZrZn2

Abstract: We show that the superconductivity observed recently in the weak itinerant ferromagnet ZrZn2 [C. Pfleiderer et al., Nature (London) 412, 58 (2001)] is due to remnants of a superconducting layer induced by spark erosion. Results of resistivity, susceptibility, specific heat and surface analysis measurements on high-quality ZrZn2 crystals show that cutting by spark erosion leaves a superconducting surface layer. The resistive superconducting transition is destroyed by chemically etching a layer of 5 µm from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…The resistivity of stoichiometric Ni 3 Al shows a pronounced NFL temperature dependence on either side of the transition, ∆ρ ∝ T n , with n somewhere between 3/2 and 5/3 (Fluitman et al, 1973;Pfleiderer, 2007;Steiner et al, 2003). At ambient pressure and in zero magnetic field Steiner et al (2003) found n = 1.65 for temperatures between about 0.5 and 3.5 K. The prefactor is comparable with that of the T 3/2 behavior of the resistivity in ZrZn 2 (Pfleiderer et al, 2001b;Yelland et al, 2005).…”
mentioning
confidence: 75%
“…The resistivity of stoichiometric Ni 3 Al shows a pronounced NFL temperature dependence on either side of the transition, ∆ρ ∝ T n , with n somewhere between 3/2 and 5/3 (Fluitman et al, 1973;Pfleiderer, 2007;Steiner et al, 2003). At ambient pressure and in zero magnetic field Steiner et al (2003) found n = 1.65 for temperatures between about 0.5 and 3.5 K. The prefactor is comparable with that of the T 3/2 behavior of the resistivity in ZrZn 2 (Pfleiderer et al, 2001b;Yelland et al, 2005).…”
mentioning
confidence: 75%
“…Here more recent work suggests that the superconductivity is not intrinsic, but due to the Zn depletion of spark eroded sample surfaces (Yelland et al, 2005).…”
Section: B Border Of Ferromagnetismmentioning
confidence: 98%
“…5 Interestingly, superconductivity originates from the surface alloy rich in Zn. 6 In addition, the spin-singlet pairing superconductivity and magnetic order parameters entwine each other in a spatially modulated pattern, which allows for their mutual coexistence in for example borocarbides, 7 CeCoIn 5 in high magnetic fields, 8,9 HoMo 6 S 8 , 10 P doped EuFe 2 As 2 , 11 and ErRh 4 B 4 .…”
mentioning
confidence: 99%